Numerical Analysis for Dynamic Instability of Electrodynamic Maglev Systems. (1995) - Cai, Y.; Chen, S.S.
Abstract : Suspension instabilities in an electrodynamic maglev system with three- and five-degrees-of-freedom DOF vehicles traveling on a double L-shaped set of guideway conductors were investigated with various experimentally measured magnetic force data incorporated into theoretical models. Divergence and flutter were obtained from both analytical and numerical solutions for coupled vibration of the three-DOF maglev vehicle model. Instabilities of five direction motion (heave, slip, roll, pitch, and yaw) were observed for the five-DOF vehicle model. The results demonstrate that system parameters such as system damping, vehicle geometry, and coupling effects among five different motions play very important roles in the occurrence of dynamic instabilities of maglev vehicles.